Femoral Neck Fracture in a Pediatric Patient with Primary Hyperparathyroidism - Mark W. Schmitt; Maxwell J. Modrak; Soumar J. Bouza; Brian G. Smith; Murillo A. Adrados (Case Reports in Orthopedics)
Case. A previously healthy 11-year-old girl underwent expedited surgical fixation of a femoral neck fracture sustained while jump-roping. After further work up, she was diagnosed with primary hyperparathyroidism. Parathyroidectomy of a hypertrophic adenoma proved curative. Now, five months post left hip surgery, the patient is pain-free and walks without a limp. Conclusion. We describe the first published case of primary hyperparathyroidism presenting as a pathologic hip fracture in a child. Although presentation with a fracture is exceedingly rare, bone pain is a frequent complaint of pediatric hyperparathyroidism. Orthopedic surgeons may find themselves the front-line caregivers for the condition.